The Impact of Collagen Fibril Polarity on Second Harmonic Generation Microscopy - Couture, Charles-André (Biophys J, 2015)
In this work, we report the implementation of interferometric second harmonic generation (SHG) microscopy with femtosecond pulses. As a proof of concept, we imaged the phase distribution of SHG signal from the complex collagen architecture of juvenile equine growth cartilage. The results are analyzed in respect to numerical simulations to extract the relative orientation of collagen fibrils within the tissue. Our results reveal large domains of constant phase together with regions of quasi-random phase, which are correlated to respectively high- and low-intensity regions in the standard SHG images. A comparison with polarization-resolved SHG highlights the crucial role of relative fibril polarity in determining the SHG signal intensity. Indeed, it appears that even a well-organized noncentrosymmetric structure emits low SHG signal intensity if it has no predominant local polarity. This work illustrates how the complex architecture of noncentrosymmetric scatterers at the nanoscale governs the coherent building of SHG signal within the focal volume and is a key advance toward a complete understanding of the structural origin of SHG signals from tissues.